PERILAKU KONSUMEN SUSU KAMBING PASTEURISASI PRODUK PETERNAKAN TELAGA RIZQY 21 DI KOTA METRO - Anjelina, Dela; Indriani, Yaktiworo; Endaryanto, Teguh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This study aims to analyze the behavior of consumers of pasteurized goat milk from Telaga Rizqy 21 livestock products.  The method used was survey method.  The number of respondents in this research was 60 consumers of pasteurized goat milk.  Data collection was conducted from November 2023 to January 2024, and analyzed by using quantitative descriptive method, employed Multiattributes Fishbein's, Customer Satisfaction Index (CSI), loyalty pyramid, and Spearman Rank.  The results show that consumers motivation in buying the milk product is due to the benefit of the product. The consumers get information from their friend related to the location where to get the product.  The main consideration of purchasing is the flavour variants. This research evaluates that an alternative when the product runs out is to buy another brand elsewhere. Purchase decisions are influenced by friends with planned purchases.  Based on study, all consumers are interested in making repeat order, with satisfied consumers reach 78.33 percent. The results of the analysis of consumer attitudes towards pasteurized goat milk are in a good category.  The level of consumer satisfaction in the satisfied category with the highest attribution score is the flavor variant.  The level of consumer loyalty based on the consumer loyalty pyramid analysis test tends to be unloyalty because the percentage of committed buyers is smaller than the value of switcher buyers. It is also found that there is a significant relationship between age income and consumer attitudes. Key words:attitude, decision making, goat milk, loyalty, satisfaction